2017
DOI: 10.1159/000479875
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic Preoptic Area and Body Weight Control

Abstract: The preoptic area (POA) of the hypothalamus is involved in many physiological and behavioral processes thanks to its interconnections to many brain areas and ability to respond to diverse humoral factors. One main function of the POA is to manage body temperature homeostasis, e.g. in response to ambient temperature change, which is achieved in part by controlling brown adipose tissue thermogenesis. The POA is also importantly involved in modulating food intake in response to temperature change, thus making it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 83 publications
(87 reference statements)
0
27
0
Order By: Relevance
“…The functions of the POA in the hypothalamus are very complicated. It has been shown that POA is a critical region for thermoregulation and energy balance (Boulant, 2000;Yu et al, 2018). Some sub-areas like the MPO region are associated with sexual behavior (Merari and Ginton, 1975;Dominguez and Hull, 2005;Wei et al, 2018).…”
Section: Innervation In the Hypothalamic Areamentioning
confidence: 99%
“…The functions of the POA in the hypothalamus are very complicated. It has been shown that POA is a critical region for thermoregulation and energy balance (Boulant, 2000;Yu et al, 2018). Some sub-areas like the MPO region are associated with sexual behavior (Merari and Ginton, 1975;Dominguez and Hull, 2005;Wei et al, 2018).…”
Section: Innervation In the Hypothalamic Areamentioning
confidence: 99%
“…Integrative temperature information in the POA is then transmitted to various brain sites that modulate physiological and behavioral thermal responses 9 , 10 . In addition to thermoregulation, the POA also monitors metabolic state and regulates food intake 11 . The dual functions of the POA in maintaining temperature and energy balance suggest the hypothesis that this region may coordinate the thermal and metabolic responses to energy deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For example, rats with POA lesions had difficulty not only maintaining core temperature but also adjusting food intake upon ambient temperature changes ( Hamilton, 1963 ; Hamilton and Brobeck, 1964 ). Despite its prominent role in regulating energy expenditure and implication in controlling food intake, the POA has not been investigated as an important brain area for body weight regulation ( Yu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%